2022
DOI: 10.1093/brain/awac387
|View full text |Cite
|
Sign up to set email alerts
|

Common neural substrates of diverse neurodevelopmental disorders

Abstract: Neurodevelopmental disorders are categorized and studied according to their manifestations as distinct syndromes. For instance, congenital prosopagnosia and dyslexia have largely non-overlapping research literatures and clinical pathways for diagnosis and intervention. On the other hand, the high incidence of neurodevelopmental comorbidities or co-existing extreme strengths and weaknesses suggest that transdiagnostic commonalities may be greater than currently appreciated. The core-periphery model holds that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 117 publications
(118 reference statements)
1
6
0
Order By: Relevance
“…Also in support of this idea, activity in a left-hemisphere mid-dorsolateral PFC area, close to the region we found in typical imagers, was associated with the processing of conscious stimuli relative to comparable but unconscious stimuli (Lau & Passingham, 2006) . Reduced long-range connectivity is a hallmark of various neurodevelopmental disorders (Sokolowski & Levine, 2023) . Within the framework of the Global Neuronal Workspace hypothesis of conscious perception (Dehaene et al, 2006;Mashour et al, 2020) , such a functional disconnection between FIN and FP networks could be interpreted as depriving visual mental imagery of its conscious experiential content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also in support of this idea, activity in a left-hemisphere mid-dorsolateral PFC area, close to the region we found in typical imagers, was associated with the processing of conscious stimuli relative to comparable but unconscious stimuli (Lau & Passingham, 2006) . Reduced long-range connectivity is a hallmark of various neurodevelopmental disorders (Sokolowski & Levine, 2023) . Within the framework of the Global Neuronal Workspace hypothesis of conscious perception (Dehaene et al, 2006;Mashour et al, 2020) , such a functional disconnection between FIN and FP networks could be interpreted as depriving visual mental imagery of its conscious experiential content.…”
Section: Discussionmentioning
confidence: 99%
“…In partial agreement with our results, Milton et al (2021) found reduced resting-state functional connectivity between PFC and the visual–occipital network in aphantasia. Reduced long-range connectivity is a hallmark of various neurodevelopmental disorders, perhaps including aphantasia (Sokolowski & Levine, 2023). Within the framework of the Global Neuronal Workspace hypothesis of conscious perception (Dehaene et al, 2006; Mashour et al, 2020), such a functional disconnection between FIN and FP networks could be interpreted as depriving visual mental imagery of its conscious experiential content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering evidence from pathogenesis and biochemical hallmarks, studies have shown mitochondrial impairment in neurodevelopmental disorders [ 12 , 13 ] but only one study considered learning disabilities [ 14 ]. Concerning evidence from neuroimaging across perception, memory, and academic domains, neurodevelopmental deficits in different cognitive areas share a reduced long-range projection between the local perceptual areas that govern consciousness and the high-level prefrontal cortex [ 15 ]. However, SLD remain a complex disease, and indeed, the current literature analyses show that new gene clusters are constantly emerging, and their protein products are involved in numerous biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…The comorbidity between learning disorders is four to five times higher in samples that have already experienced marked problems in one academic domain compared to the full population [ 17 ] and high comorbidities exist even with other neurodevelopmental and emotional or behavior disorders (i.e., attention deficit hyperactivity disorder, conduct disorder, anxiety, depression [ 18 , 19 ]). The variability of multimodal associative cortical connectivity may reflect a common origin in seemingly disparate neurodevelopmental disorders: this framework helps describe the comorbidities of neurodevelopmental disorders [ 15 ].…”
Section: Introductionmentioning
confidence: 99%